Characterization of internal phosphorus loading in the sediment of a large eutrophic lake (Lake Taihu, China). (15th October 2022) - Yin, Hongbin; Zhang, Man; Yin, Peng; Li, Jiying
Highlights: Sediment internal P loading differs in algal-dominated zone and grass-dominated zone. Higher mobile P and P flux were found in the sediment of algal-dominated zone (ADZ). Ca–P had the main percentage of TP in the sediment of a grass-dominated zone (GDZ). Firmicutes and Proteobacteria prefer mobile P and Ca–P in sediment, respectively. Different strategies are needed for sediment internal P control in ADZ and GDZ. Abstract: Lake Taihu suffers from severe algal blooms every year, which is attributed primarily to the release of sediment phosphorus (P), namely the internal P loading. However, the overall internal P loading and the P hotspots in sediment have not been fully studied. This paper presents several methods, including sequential P extraction, the use of diffusive gradient in thin film (DGT), and intact core incubation to give a detailed investigation of sediment internal P loading as well as its roles in algal dominated zones (ADZs) and grass dominated zones (GDZs) in Lake Taihu. Sediment microbial composition was also analyzed to investigate its relationship with P fractions. The results indicate that the total P and the mobile P fraction in the ADZ sediments are generally higher than those of the GDZ sediments. The percentage of sediment mobile P to TP is similar to the mobile P in their distributions. In contrast, calcium bound P accounts for most of the TP in GDZ, while mobile P contributes the most to TP in ADZ. Overall, sediment can release 256 tons of TP and 217 tons of soluble reactive phosphorus (SRP) over a period of six months in the warmer seasons. Similarly, a high concentration of DGT-measured P was observed in ADZs that are recognized as P hotspots in Lake Taihu. Sediments in ADZ and GDZ was dominated by the bacteria Firmicutes and Proteobacteria, respectively and which were closely related with mobile P and calcium bound P in sediment, respectively. GZD seems to be able to retain more P in sediments, thereby reducing its contribution to of internal P loading. These results indicate that the difference in sediment composition between ADZ and GDZ affects their roles in sediment internal P loading, therefore, different management strategies should be used to combat sediment internal P loads in the two zones. Graphical abstract: Image, graphical abstract